Substitution of Tapioca Flour With Purple Sweet Potato Flour in The Production of Broiler Chicken Meatballs - Hasan, Hasanuddin; Rasuli, Nur; Yunus, Muhammad (Jurnal Peternakan Nusantara, 2026)
This study aims to evaluate the effect of substituting tapioca flour with purple sweet potato flour on the physical and sensory characteristics of broiler chicken meatballs. A Completely Randomized Design (CRD) was applied with four treatments: P0 (0%), P1 (5%), P2 (10%), and P3 (15%) purple sweet potato flour, each repeated four times. Observed parameters included water holding capacity, cooking loss, and organoleptic attributes (color, aroma, taste, and texture). ANOVA results showed no significant differences (P>0.05) in water holding capacity and cooking loss, but significant effects (P<0.05) were observed on all sensory parameters. Treatment P2 (10%) yielded the highest sensory scores, particularly in taste and texture, without compromising physical quality. The addition of purple sweet potato flour enhanced the visual appeal and flavor due to its anthocyanin and dietary fiber content. These findings suggest that substituting 10% tapioca flour with purple sweet potato flour is a viable innovation to develop healthier and more appealing broiler chicken meatballs using local functional ingredients.